2020
DOI: 10.1016/j.celrep.2020.107893
|View full text |Cite
|
Sign up to set email alerts
|

Cofilin Loss in Drosophila Muscles Contributes to Muscle Weakness through Defective Sarcomerogenesis during Muscle Growth

Abstract: SUMMARY Sarcomeres, the fundamental contractile units of muscles, are conserved structures composed of actin thin filaments and myosin thick filaments. How sarcomeres are formed and maintained is not well understood. Here, we show that knockdown of Drosophila cofilin ( DmCFL ), an actin depolymerizing factor, disrupts both sarcomere structure and muscle function. The loss of DmCFL also results in the formation of sarcomeric protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 88 publications
(125 reference statements)
3
32
0
Order By: Relevance
“…Quantification of larval crawling velocity by tracking larval movement serves as a proxy for muscle function and can help understand how mutations in genes involved in muscle development and function can affect muscle contraction, thereby impairing larval movement. In control larvae, larval locomotion velocity increases as the larvae progress through the instars [ Figure 5 I, ( Balakrishnan et al., 2020 )]. This increase in locomotion velocity throughout larval stages is consistent with an increase in muscle size that occurs during the instars ( Balakrishnan et al., 2020 , Demontis and Perrimon, 2009 , Bawa et al., 2020 ).…”
Section: Expected Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…Quantification of larval crawling velocity by tracking larval movement serves as a proxy for muscle function and can help understand how mutations in genes involved in muscle development and function can affect muscle contraction, thereby impairing larval movement. In control larvae, larval locomotion velocity increases as the larvae progress through the instars [ Figure 5 I, ( Balakrishnan et al., 2020 )]. This increase in locomotion velocity throughout larval stages is consistent with an increase in muscle size that occurs during the instars ( Balakrishnan et al., 2020 , Demontis and Perrimon, 2009 , Bawa et al., 2020 ).…”
Section: Expected Outcomesmentioning
confidence: 99%
“…In control larvae, larval locomotion velocity increases as the larvae progress through the instars [ Figure 5 I, ( Balakrishnan et al., 2020 )]. This increase in locomotion velocity throughout larval stages is consistent with an increase in muscle size that occurs during the instars ( Balakrishnan et al., 2020 , Demontis and Perrimon, 2009 , Bawa et al., 2020 ). Mutations in genes affecting larval locomotion thus far have predominantly decreased locomotion, with very few mutations identified that increase locomotion of the larva ( Camuglia et al., 2018 ).…”
Section: Expected Outcomesmentioning
confidence: 99%
See 3 more Smart Citations